2020
DOI: 10.1096/fj.202000154rr
|View full text |Cite
|
Sign up to set email alerts
|

TRPC1/4/5 channels contribute to morphine‐induced analgesic tolerance and hyperalgesia by enhancing spinal synaptic potentiation and structural plasticity

Abstract: Opioid analgesics remain the mainstay for managing intractable chronic pain, but their use is limited by detrimental side effects such as analgesic tolerance and hyperalgesia. Calcium‐dependent synaptic plasticity is a key determinant in opiates tolerance and hyperalgesia. However, the exact substrates for this calcium‐dependent synaptic plasticity in mediating these maladaptive processes are largely unknown. Canonical transient receptor potential 1, 4, and 5 (TRPC1, 4, 5) proteins assemble into heteromultimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Although our present results do not support the hypothesis that spinal TRPC4/C5 had a key role in mediating the hypersensitivity effect induced by netrin-1, this proposal does not exclude the potential pronociceptive role of spinal TRPC4/C5 in other conditions. In line with this caveat, a recent study reported that morphine-induced analgesic tolerance and hyperalgesia were associated with increased expression of spinal TRPC4/C5 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our present results do not support the hypothesis that spinal TRPC4/C5 had a key role in mediating the hypersensitivity effect induced by netrin-1, this proposal does not exclude the potential pronociceptive role of spinal TRPC4/C5 in other conditions. In line with this caveat, a recent study reported that morphine-induced analgesic tolerance and hyperalgesia were associated with increased expression of spinal TRPC4/C5 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…If one infers from the existence of a negative slope region in mGluR1/5-induced current, heteromeric TRPC1/5 could be abundant in CA3 pyramidal neurons. Heteromeric channels comprised of all three members of the TRPC1/4/5 subgroup may also exist in some neurons (85).…”
Section: Trpc4 and Tprc5mentioning
confidence: 99%
“…Heteromeric assemblies of TRP channel subunits are known to be formed within their subfamily and moreover with TRP channel subunits from other subfamilies, as it has been demonstrated for heteromeric assemblies of TRPP2/C1 in pig kidney epithelial cells [ 21 ], or TRPC1/V6 and TRPML/V5 in HEK293 cells [ 60 , 61 ]. Heteromerization of three different TRP channel subunits has also been described, e.g., for TRPC3/C6/C7 [ 62 ], TRPC1/C4/C5 [ 63 ], or TRPV4/C1/P2 [ 64 ] although heteromerization of two TRP channel subunits seems to be more commonly found [ 20 ]. It seems fair to speculate that with an increasing number of different TRP channel subunits being co-expressed in the same tissue or cell type, the probability for heteromerization increases which in turn may serve as a mechanism to fine-tune cellular responses to tissue-specific environmental stimuli [ 65 ].…”
Section: Heteromeric Trp Channel Assemblies and Their Molecular Mechanismsmentioning
confidence: 99%